Severe hyperphosphataemia and metabolic acidosis after administration of phosphate-containing enema in a 10-year-old girl – case report and review of literature - Pawlik, Weronika; Drzonek, Patrycja; Nowak, Katarzyna; Mokrzycka, Małgorzata; Zalewska-Szymanowicz, Aleksandra (Pediatria Polska - Polish Journal of Paediatrics, 2020)
Constipation is among the most common complaints in GPs’ offices, affecting over 10% of children reporting to the doctor [1]. Due to the COVID-19 pandemic, access to specialist care has become difficult, which has led to neglect of diagnosis and managing chronic diseases. We present a case of a 10-year-old girl admitted to the emergency department (ED) with symptoms of severe constipation and abdominal pain and a history of ongoing constipation and faecal soiling for 6 months. In the ED she was given a sodium-phosphate enema twice. After a few hours she developed life-threatening hyperphosphataemia, hypocalcaemia, and metabolic acidosis. The presented patient presents an example of severe, chronic, and improperly treated constipation with an extremely rare side effect of a sodium-phosphate enema. It is important to underline that monitoring after the procedure and quick and proper treatment, if the mentioned effect occurs, can save the patient’s life.